Rotational motion and organization studies of cell membrane proteins - Zhang, Dongmei, author; Barisas, B. George, advisor; Van Orden, Alan, committee member; Henry, Chuck, committee member; Roess, Deborah A., committee member; Crans, Debbie, committee member (Colorado State University. Libraries, 2016)
Cell membranes are dynamic structures with complex organization. The complexity of the cell membrane arises from intrinsic membrane structure, membrane microdomains within the plasma membrane and the membrane cytoskeleton. Plasma membrane receptors are integral membrane proteins with diverse structures and functions which bind specific ligands to trigger cellular responses. Due to compartmentalization of the plasma membrane and the formation of membrane microdomains, receptors are distributed non-homogeneously in the cell membrane bilayer. Both lateral and rotational diffusion of membrane receptors reflects different kinds of intermolecular interactions within the plasma membrane environment. Understanding protein diffusion within the membrane is very important to further understanding biomolecular interactions in vivo during complex biological processes including receptor-mediated signaling. Rotational diffusion depends linearly on the in-membrane volume of the rotating proteins. Relative to lateral diffusion, rotational diffusion is a more sensitive probe of an individual molecule’s size and local environment. We have used asymmetric quantum dots (QD) to conduct imaging measurements of individual 2H3 cell Type I Fcε receptor rotation on timescales down to 10 msec per frame. We have also used time-tagged single photon counting measurements of individual QD to examine μsec timescales, although rapid timescales are limited by QD emission rates. In both approaches, decays of time-autocorrelation functions (TACF) for fluorescence polarization fluctuations extend into the millisecond timescale, as implied by time-resolved phosphorescence anisotropy results. Depending on instrumental parameters used in data analysis, polarization fluctuation TACFs can contain a contribution from the intensity fluctuation TACF arising from QD blinking. Such QD blinking feed-through is extremely sensitive to these analysis parameters which effectively change slightly from one measurement to another. We discuss approaches based on the necessary statistical independence of polarization and intensity fluctuations to guarantee removal of a blinking-based component from rotation measurements. Imaging results demonstrate a range of rotational behavior among individual molecules. Such slow motions, not observable previously, may occur with large signaling complexes, which are important targets of study in cell biology. These slow motions appear to be a property of the membrane itself, not of the receptor state. Our results may indicate that individual mesoscale membrane regions rotate or librate with respect to the overall cell surface. The luteinizing hormone receptor (LHR) is a seven transmembrane domain receptor and a member of the GPCR family. It is located on luteal cells, granulosa and theca cells in females. Understanding how these protein receptors function on the plasma membrane will lead to better understanding of mammalian reproduction. LHR becomes aggregated upon binding hCG when receptors are expressed at physiological numbers. Binding of hormone to LHR leads to activation of adenylate cyclase (AC) and an increase in intracellular cyclic AMP (cAMP). ICUE3 is an Epac-based cAMP sensor with two fluorophores, cyan fluorescent protein (CFP) and the YFP variant, cpVenus, and a membrane-targeting motif which can be palmitoylated. Upon binding cAMP, ICUE3 undergoes a conformational change that separates CFP and YFP, significantly reducing FRET and thus increasing the ratio of CFP to YFP fluorescence upon excitation with an arc lamp or 405nm laser source. Hence we have investigated hLHR signal transduction using the cyclic AMP reporter probe, ICUE3. A dual wavelength emission ratio (CFP/YFP) imaging method was used to detect a conformational change in ICUE3 upon binding cAMP. This technique is useful in understanding the sequence of intercellular events following hormone binding to receptor and in particular, the time course involved in signal transduction in a single cell. Our data suggested that CHO cells expressing ICUE3 and directly treated with different concentrations of cAMP with saponin can provide a dose-dependent relationship for changes in intracellular cAMP levels. Forskolin (50μM) causes maximal activation of the intracellular cAMP and an increase in the CFP/YFP emission ratio. In CHO cells expressing both ICUE3 and hLHR-mCherry, the CFP/YFP ratio increased in cells treated with forskolin and in hCG- treated cells. In flow cytometry studies, similar results were obtained when CHO cells expressed < 60k LHR-mCherry per cell. Our results indicate that ICUE3 can provide real time information on intracellular cAMP levels, and the ICUE3 is a reliable cAMP reporter can be used to examine various aspects of LH receptor-mediated signaling.
Keywords: Fcε type I receptor; luteinizing hormone receptor function; rotation; ICUE3 cAMP reporter; cell surface receptors; nanoparticle probes